Conclusions of a meeting of the Cabinet held at 10 Downing Street, S.W.1, on Tuesday, 18th November, 1958, at 11 a.m - Great Britain; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1958)
Includes discussion of contemporary topics in world politics, and the renaming of Empire Day to Commonwealth Day